Dampak Perilaku Remaja Pengguna Narkoba di Nagari Lubuk Gadang Kecamatan Sangir Kabupaten Solok Selatan - Rahman, Zaldi Yanto Anwar (Pendidikan Sosiologi, 2014)
Adolescenes is a periode of transition, where these days there is atendency to do things that are negative because the teenage years are times of the search for identity. Drug abuse is one-of juvenile delinquency in the Lubuk Gadang Villages. Some of the reasons teens use drugs to be a factor, regardless of the negative impact on the Lubuk Gadang Village communities of South Solok District of Sangir. Therefore, this study aims to description. (1) The cause of adolosecent drug user and describe. (2) the impact of the behavior of young drug users in Lubuk Gadang Village District of Sangir South Solok.The theory used in this research is the sosiology of behavioral theory proposed by Skinner. Where the sociology of behavioral theory focuses on the relationship betwen the result of the behavioral that occurs within the actor with the actorâs behavior. This study uses qualitative and descriptive studies. Informants in this study is a community and village leaders Lubuk Gadang District of Sangir South Solok and adolescent involved in drug cases in Lubuk Gadang Village District of Sangir South Solok, the number of informants as much as 22 (twenty-two). By three method of data collection as follows: (1) observation, (2) interview, (3) and the study documents.From the result of this study indicate that the causes of adolescent drug use are: (1) individual factors which include: (a) the influence of curiosity and, (b) broken heart. (2) Enviromental factors that include: (a) environmen of association playmates, and (b) the work environment. As for impact of the behavior of young drug users are: (1) disturbing the public, (a) as do theft and, (b) fights. (2) Damaging the next generation. (3) Disturbing public order by behavior: (a) brought loud motorcyle near mosque, and (b) create excitement at night.